Digitalization in public service: effectiveness analysis of information and communication platforms of government bodies in providing services to the population - M. S. Nakhusheva; S. A. Kirzhinova (Вестник Майкопского государственного технологического университета, 2025)
Introduction. The article considers the issues of the effectiveness of information and communication platforms (ICP) of government bodies in providing services to the population. The relevance is substantiated by the fact that ICPs are becoming an integral part of management processes, allowing not only to simplify citizens' access to state and municipal services, but also to ensure transparency of decision-making, prompt feedback and strengthening trust in government institutions.The methods and materials used in the research are structural and functional analysis, content analysis – a study of Internet sites of government bodies at various levels, as well as a comparison method when comparing them according to various criteria.The Research results. Unlike the commercial sector, where digital transformation is focused primarily on economic benefits, in public service such aspects as ensuring equal access to services, increasing government transparency, taking into account regional specifics and a differentiated approach to different groups of the population come to the fore.Discussion and conclusion. To analyze the effectiveness of the ICP, three levels of government in the Russian Federation have been considered: federal, regional and municipal ones. This approach allowed us to identify common features and differences in the implementation of digital solutions at different levels of government. The analysis has shown that federal-level digital platforms are superior to regional and municipal ones in functionality, convenience and relevance, but are inferior in their focus on the daily needs of citizens. Regional platforms occupy an intermediate position, combining information and basic services, while municipal ones focus on local tasks, but are limited by technical and resource capabilities.